KAJIAN SOSIOLOGI SASTRA DAN NILAI TOLERANSI PADA NOVEL KAMBING DAN HUJAN KARYA MAHFUD IKHWAN SERTA RELEVANSINYA DENGAN MATERI AJAR APRESIASI SASTRA DI SMA KELAS XII - Ayu Sukma; Andayani Andayani; Yant Mujiyanto (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study aimed to describe: (1) social background novel Kambing dan Hujan, (2) the social background of the author, (3) a response from readers based on social background, (4) the value of tolerance, (5) the relevance of novel Kambing dan Hujan with teaching materials appreciation of literature in high school. This study is a qualitative research approach of sociology of literature. The data collection technique used is the analysis of documents and interviews. Analysis of the data used is an interactive model. The conclusions of this study are: (1) aspects of social background in the novel: habits, customs, traditions, ways of thinking and behaving, beliefs, and outlook on life; (2) social background author: born in Lamongan, East Java, on May 7, 1980. Living in Yogyakarta and work as a novelist, editor, and facilitator in Bengkel Menulis Gerakan Literasi Indonesia. Novel Kambing dan Hujan written based on the experience of author when living in the region of origin; (3) a response from the reader, the novel nice and attractive and provide a positive influence; (4) the value of tolerance in the novel: the value of tolerance to the habit, circumstances, views, and behavior; (5) novel Kambing dan Hujan relevant with teaching materials appreciation of literature in high school because having already qualified identification of teaching material learning and in accordance with the teaching materials in the syllabus Indonesian subjects Curriculum 2013 revised edition 2016.